Controlling of electrical and interface state density properties of ZnO:Co/p-silicon diode structures by compositional fraction of cobalt dopant - Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2011)
The heterojunction diodes based on cobalt doped zinc oxide (ZnO) were prepared by so-gel deposition method. The compositional fraction of cobalt dopant was varied to control the electrical parameters of the diode. Atomic force microscopy was used to determine the structural properties of ZnO:Co films. The ZnO:Co films have a microfiber structure and the structure of microfibers was changed with the cobalt dopant. The ideality factor values of 5% and 15% Co doped ZnO:Co/p-Si diodes were determined to be 3.49 and 7.51, respectively. The barrier height of the ZnO:Co/p-Si diodes were found to vary from 0.75 eV to 0.78 eV. It is concluded that the electrical and interface state density properties of ZnO:Co/p-Si diodes can be controlled by compositional fraction of cobalt dopant. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Doped Zno Nanowires; Temperature Ferromagnetism; Optical-Properties